Analysis of Factors and Actors Contributing to Writing Difficulties Among Lower Grade Students - Lutfia Permatasari; Sapri Sapri (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to identify the factors causing writing difficulties among lower-grade students at MIN 7 Bahorok District and to analyze the impact of the interaction between internal and external factors on students’ early writing skills. The study employed a descriptive qualitative approach to obtain an in-depth understanding of the conditions occurring in the writing learning process. The data sources consisted of primary data obtained through interviews with the principal, a grade II teacher, and students, as well as secondary data in the form of books, journals, and school documents. Data were collected through observation, interviews, and documentation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that students’ writing difficulties in the lower grades are influenced by several factors, namely internal factors such as basic abilities, motivation, and learning readiness; psychological factors and learning interest; family environmental factors; school factors and teaching methods; as well as learning facilities and infrastructure. In addition, the interaction between internal and external factors has a significant impact on students’ early writing abilities. Positive impacts are seen in students who have high motivation and receive support from their families and teachers, enabling them to recognize letters more quickly, arrange words into simple sentences, and become more confident in writing. Conversely, negative impacts are observed in students who lack support and have low motivation, resulting in difficulty recognizing letters, untidy handwriting, easy boredom, lack of focus, and slow completion of writing tasks.